2002
DOI: 10.1046/j.1365-2249.2002.01931.x
|View full text |Cite
|
Sign up to set email alerts
|

T-cell reactivity to glutamic acid decarboxylase in stiff-man syndrome and cerebellar ataxia associated with polyendocrine autoimmunity

Abstract: SUMMARYAntibodies to glutamic acid decarboxilase (GAD-Abs) are present in the serum of 60-80% of newly diagnosed type 1 diabetes (DM1) patients and patients with autoimmune polyendocrine syndrome (APS) associated with DM1. Higher titre of GAD-Abs are also present in the serum of 60% of patients with stiff-man syndrome (SMS) and all reported patients with cerebellar ataxia associated with polyendocrine autoimmunity (CAPA). Several studies suggest that GAD-Abs may play a critical role in the pathogenesis of SMS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 44 publications
(52 reference statements)
0
19
0
2
Order By: Relevance
“…T-cell responses and levels of GADA have been studied only in SPS patients who were already affected by T1D. [24, 28, 50] An early study by Hummel and co-workers demonstrated a weak but detectable T-cell response to GAD65 and IA-2 with IFN-γ production that decreased in response to immunosuppressive therapy. [24] Schloot et al reported lack of primary T-cell response to GAD65 in a non-diabetic SPS patient.…”
Section: Discussionmentioning
confidence: 99%
“…T-cell responses and levels of GADA have been studied only in SPS patients who were already affected by T1D. [24, 28, 50] An early study by Hummel and co-workers demonstrated a weak but detectable T-cell response to GAD65 and IA-2 with IFN-γ production that decreased in response to immunosuppressive therapy. [24] Schloot et al reported lack of primary T-cell response to GAD65 in a non-diabetic SPS patient.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the T-cell clones in SPS produce Th2 cytokines supporting an antigen-driven collaboration between T and B cells leading to a sustained intrathecal production of oligoclonal anti-GAD IgG antibodies 65. Furthermore, a Th2 anti-inflammatory response in SPS has been proposed as a protective mechanism against the development of T1D in the majority of patients with SPS 67. The T-cell response in patients with SPS seem to be different from those with cerebellar ataxia and anti-GAD antibodies, with the latter having higher IFNγ production and lower proliferative response to GAD65 by T-cells 67.…”
Section: Pathogenesis and Pathophysiologymentioning
confidence: 99%
“…Furthermore, a Th2 anti-inflammatory response in SPS has been proposed as a protective mechanism against the development of T1D in the majority of patients with SPS 67. The T-cell response in patients with SPS seem to be different from those with cerebellar ataxia and anti-GAD antibodies, with the latter having higher IFNγ production and lower proliferative response to GAD65 by T-cells 67. It is unclear what mechanisms are involved in the reactivation of T cells, once inside the CNS.…”
Section: Pathogenesis and Pathophysiologymentioning
confidence: 99%
“…Furthermore, the intrathecal production of GAD-specific antibodies was described in previous studies that demonstrated elevated GAD-Ab indices in the majority of patients with various GADassociated neurological syndromes (Arino et al, 2014;Dalakas et al, 2001b;Malter et al, 2010). Given that neurological manifestations with high serum titers of GAD-Abs were frequently accompanied by polyendocrine autoimmunity (Costa et al, 2002), the absence of coexisting autoimmune diseases in our subjects also corresponded to humoral immunity limited to the CNS. In addition to GAD-Abs, Results are presented as number (%) or median (range).…”
Section: Discussionmentioning
confidence: 49%